At Macqueripe, Trinidad, B.W.I. - (:unkn) unknown (Pereira and Co. Ltd.,[Trinidad and Tobago], 2011)
The postcard shows beach goers at Macqueripe Bay, Chaguaramas, Trinidad. Macqueripe Bay is situated at the end of Tucker Valley Road in Chaguaramas. The beach was a popular resort in the 1930's and 1940's but access was restricted in 1944 when the Trinidad and Tobago Government leased the area to the United States military. In the postcard, changing rooms and bathroom facilities can be seen on the beach. This used postcard is dated 1940 and affixed is a three cents Trinidad and Tobago postage stamp.
Colour: Black and white; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; 1940; Inlets--Trinidad and Tobago; Beaches--Trinidad and Tobago; Beachgoers--Trinidad and Tobago; Bays--Trinidad and Tobago; Macqueripe Bay